Hydro-mechanical analysis of a surficial landslide triggered by artificial rainfall: the Ruedlingen field experiment. Issue 2 (6th February 2021) - Sitarenios, Panagiotis; Casini, Francesca; Askarinejad, Amin; Springman, Sarah
Abstract : This paper interprets the hydromechanical behaviour of a steep, forested, instrumented slope during an artificial rainfall event, which triggered a shallow slope failure 15 h after rainfall initiation. The soil's mechanical response has been simulated by coupled hydro-mechanical finite-element analyses, using a critical state constitutive model that has been extended to unsaturated conditions. Failure occurs within a colluvium shallow soil cover, characterised as a silty sand of low plasticity. The hydraulic and mechanical parameters are calibrated, based on an extended set of experimental results, ranging from water retention curve measurements to triaxial stress path tests under both saturated and unsaturated conditions. Rainfall is simulated as a water flux at the soil surface and suitable boundary conditions account for the hydromechanical interaction between the soil cover and the underlying bedrock. The results are compared with field data of the mechanistic and the hydraulic responses up to failure and are found to provide a very satisfactory prediction. The study identifies water exfiltration from bedrock fissures as the main triggering agent, resulting in increased pore pressures along the soil–bedrock interface, reduced available shear strength and cause extensive plastic straining, leading to the formation and propagation of a failure surface.